Protection of Karst in the Philippines - Restificar, Sonata Dulce F.; Day, Michael J.; Urich, Peter B. (Acta Carsologica, 2006)
The article presents an overview of the current status of karst protection in the Philippines. Prior studies indicate that of the 35,000km2 of karst landscape in the country, about 29% is protected . However, protection of karst has not to date been a priority of the Philippine government, and the country has no existing legislation that is directly decreed for protection and conservation of karstlands. Most contemporary karst protection is indirect, in that the karst is located within protected areas established for other, although often related reasons, such as ecological conservation, water supply protection and tourism. However, it appears that the Philippine government is gradually recognizing explicitly the need to protect karst landscapes. The establishment of the National Caves and Cave Resources Management and Protection Act in 2001 and the inclusion of karst water resources in the country’s National Action Plan (NAP) under the United Nations Convention to Combat Desertification (UNCCD) are significant steps towards explicit protection of karst areas. Although the existing legislation only addresses specific facets of karst landscape, it may stimulate additional programs and legislation that will more broadly protect karst landscapes nationally.